Pemikiran Hadis KH. M. Hasyim Asy’ari dan Kontribusinya terhadap Kajian Hadis di Indonesia - Afriadi Putra (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2016)
This article describes the opinion of KH. M. Hasyim Asy’ari, one of the Indonesian Hadith scholars, and his contribution to the study of Hadith in Indonesia. This study is important to understand the dynamic of Hadith study in Indonesia that experienced stagnancy for certain period. The twentieth century marked as the rising of Hadith study in Indonesia by the emergence of many Hadith books of Arabic languages, their translations and the scholars opinion related to Hadith. The book of risālah ahlu al-sunnah wa al-jamā’ah is among those books that was written in the beginning of the twentieth century. This book played a significant role at that time as a guidance for Muslim society in facing modernity. The content of this book provides basic themes related to religious experiences of the community. This book is also represented the opinion of KH. M. Hasyim Asy’ari related to Hadith, as an Indonesian Muslim scholar who received isnād Hadith (the chain of Hadith transmission) from his teacher Syeikh Mahfudz Termas.